2000
DOI: 10.1016/s0891-5849(00)00275-6
|View full text |Cite
|
Sign up to set email alerts
|

Two-photon microscopy of aorta fibers shows proteolysis induced by LDL hydroperoxides

Abstract: Abstract-Oxidatively modified LDL mimics several aspects of atherogenesis. In this disease, degradation of the matrix proteins' network also occurs. By a new morphological ex vivo approach, not requiring sample processing, we explored the relationship between the degradation of matrix protein and oxidatively modified LDL. Two-photon excitation fluorescence microscopy images of fresh cross-section rings of rat aorta, acquired while the sample was maintained in a glucose-and oxygen-supplemented buffer, showed st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 39 publications
2
10
0
1
Order By: Relevance
“…1d). Such autofluorescence is in agreement with earlier findings for elastin [22]and collagen [25, 26]. Note that collagen and elastin fibers appeared slightly thicker than in figure 1c.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…1d). Such autofluorescence is in agreement with earlier findings for elastin [22]and collagen [25, 26]. Note that collagen and elastin fibers appeared slightly thicker than in figure 1c.…”
Section: Resultssupporting
confidence: 92%
“…These studies also indicate that penetration depth of TPLSM varies between tissues. However, in atherosclerosis research TPLSM has only found very limited, and primarily ex vivo, applications [22, 23]. To our knowledge, penetration depth has not been determined in blood vessels so far.…”
Section: Introductionmentioning
confidence: 99%
“…The fluorescence lifetime found for the elastine autofluorescence is τ = 2.05 ± 0.05 ns. This corresponds with values found before 27 . For the SYTO in the smooth muscle cells a lifetime of τ = 3.4 ± 0.05 ns is found.…”
Section: Resultssupporting
confidence: 91%
“…In addition, photobleaching, -damage and -toxicity are drastically reduced [8], enabling imaging of delicate structures in viable tissue. Recently, TPLSM was established as a valuable tool for imaging of blood vessels [4,9,10,11], skeletal muscle arterioles [12], and microvasculature of the human uterus [13]. However, the blood vessels were very small [12], still treated with a fixative, freeze-thawed and sliced, or casted in hot (>40°C) agarose gel, resulting in structural alterations and loss of functionality [14].…”
Section: Introductionmentioning
confidence: 99%